(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Basic life support (BLS) is a crucial component of emergency resuscitation care that can save lives in cases of sudden cardiac arrest, heart attack, stroke, or foreign body airway obstruction. The effectiveness of cardiopulmonary resuscitation (CPR) has been linked to improved quality of life, increased neurological recovery, and a patient's ability to return to work after sudden cardiac arrest (SCA). However, there are differences in sudden cardiac arrest survival rates across regions, partially influenced by the time delay between cardiac arrest and the initiation of chest compressions. This study aims to assess the knowledge and awareness level of basic life support among Saudi medical students. Methods: This was a cross-sectional study conducted in Saudi Arabia from 2024 to 2025. The study population consisted of male and female Saudi medical students enrolled in public and private universities, aged eighteen and above. A sample size of 380 participants was calculated using the Raosoft sample size calculator. Data was collected using a questionnaire and analyzed using SPSS software version 25. Results: Regarding the knowledge and awareness of BLS, there was a generally positive recognition of BLS, with 89.6% (N 752) identifying it correctly. However, there were significant gaps in immediate response actions, as only 6.9% would initiate chest compressions upon encountering an unresponsive individual. Knowledge of CPR metrics was variable; while 65.7% accurately identified the ideal chest compression rate, only 31.9% recognized the abbreviation for Automated External Defibrillator (AED). Alarmingly, only 10.1% exhibited high knowledge levels, with 54% classified as low in BLS understanding. The study also found significant correlations between BLS knowledge and factors such as gender, age, nationality, academic level, and GPA, but no significant relationship with residential area. Conclusion: In conclusion, this study highlights a concerning gap in the knowledge and awareness of BLS among Saudi medical students. While some understanding exists, a significant portion demonstrated insufficient knowledge necessary for effective emergency response. Addressing these deficiencies through enhanced training programs is crucial to improving survival outcomes in cardiac emergencies.